2006
DOI: 10.1159/000092124
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Isolated Tonsillar Hypertrophy with Body Mass Index

Abstract: Objective: The purpose of this study was to investigate the relationship between tonsillar hypertrophy and body mass index (BMI). Material and Methods: This is a cross-sectional study which was conducted in three primary schools located in Duzce. A total of 1,282 children between 7 and 12 years of age were evaluated and the size of their tonsils was investigated with regard to height and weight. This study was performed in the course of school screening, and the correlation between estimated tonsil size and BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…In evaluating the relationship of adenotonsillar hypertrophy with BMI, it was found that BMI in growth percentiles was very low in 40.1% of patients, and also 40.4% had proportional weight to age, while 5.1% was overweight, and 14.4% had too much weight (obese). In previous studies, BMI percentiles below 2 were malnourished, between 2 and below 91 were normal, and above 91 considered obese, whereas in our study, based on the latest reference changes, the percentiles below 5% were low weight, 50% to 85% were proportional, and 85% to 95% were overweight and above 95% were obese [16].…”
Section: Discussioncontrasting
confidence: 67%
“…In evaluating the relationship of adenotonsillar hypertrophy with BMI, it was found that BMI in growth percentiles was very low in 40.1% of patients, and also 40.4% had proportional weight to age, while 5.1% was overweight, and 14.4% had too much weight (obese). In previous studies, BMI percentiles below 2 were malnourished, between 2 and below 91 were normal, and above 91 considered obese, whereas in our study, based on the latest reference changes, the percentiles below 5% were low weight, 50% to 85% were proportional, and 85% to 95% were overweight and above 95% were obese [16].…”
Section: Discussioncontrasting
confidence: 67%
“…Enlargement of tonsils and adenoids is a common finding in children but the etiology remains controversial. In children, there is no correlation between hypertrophic tonsils and the body mass index [13]. The weight of normal tonsils in children is not well documented in anatomy literature; however, the mean weight of the tonsillectomy specimens from pathologic examination was shown to be 7.3 g in children between the ages of 2 and 12 years with 63% of it falls between 5 and 8 g [14].…”
Section: Discussionmentioning
confidence: 96%
“…Since some authors have shown no association between size of tonsillar hypertrophy and BMI [25,26], we hypothesize that grade of tonsillar hypertrophy is not directly correlated to BMI. Other factors may affect BMI and grade of tonsillar hypertrophy in a concordant manner, but if the responsiveness of BMI and grade of tonsillar hypertrophy are different, there may be low or no correlation between these variables.…”
Section: Discussionmentioning
confidence: 74%